Correlation analysis of marks for mathematics and prognosis of results of examinations - Raulynaitis, Juozas; Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2002)
In this article a correlational analysis of different marks for mathematicas of those who whe admitted to the Faculty of Construction of the Vilnius Gediminas Technical University in 2001 is carried out.